A Retrospective, Cross-Sectional Study on the Prevalence of Hyperuricemia Using a Japanese Healthcare Database - Shingo HIGA; Mizuki YOSHIDA; Daisuke SHIMA; Yoichi II; Shigeru KITAZAKI; Yuji YAMAMOTO; Yoko FUJIMOTO (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the prevalence of hyperuricemia (HU) considering both serum uric acid (SUA) levels and medication status of urate-lowering drugs (ULDs), and the association between HU and its comorbidities using a Japanese healthcare database. Materials and Methods: The study population consisted of 60,828 subjects who had at least one serum uric acid measurement between the fiscal years (FYs) 2010 and 2014 in a Japanese employment-based health insurance database (MinaCare Co., Ltd., Tokyo, Japan), which includes mutually linked medical/pharmaceutical claims data and health check-up data. Hyperuricemia was defined as a SUA level >7.0 mg/dL of the health check-up data and/or a prescription for a ULD. The association between HU and comorbidities were analyzed by comparing the prevalence of HU of each subgroup defined by presence or absence of comorbidity. Results: The prevalence of HU in FY 2014 was 26.8% [95% confidence interval (CI): 26.2 to 27.3%] in male subjects and 0.9% (95% CI: 0.7 to 1.0%) in female subjects. According to the analyses by sex and age, a trend of increasing prevalence with age was observed in both males and females. The prevalence of HU remained stable both in males and females from FYs 2010 to 2014. The positive association between HU and well-known comorbidities were confirmed with the exception of diabetes mellitus and smoking status in male subjects. Conclusion: Our results provided a more accurate prevalence of HU in Japanese population. It is important to increase the awareness on HU in the society to reduce the burden of HU-related diseases.